Quality of life among patients with arthritis seeking outpatient care at a government secondary health care centre, Anekal taluk - Vijay, Christy; G., Melvin Kumar; K., Anand; Peter, Paul; T., Annisa M.; Fathima, Farah Naaz; K., Rajitha; Ramesh, Naveen (International Journal Of Community Medicine And Public Health, 2018)
Background: Arthritis means inflammation of the joints. Arthritis can be caused due a variety of local and systemic illnesses, the most common among them being osteoarthritis and rheumatoid arthritis. Arthritis can affect men, women and children. Determining the quality of life among osteoarthritis patients will provide important information for planning future cost effective preventive strategies and health care services. Methods: This was a cross-sectional study conducted among 199 symptomatic arthritis patients. Arthritis impact measurement scale 2 (AIMS 2) was administered to assess Health-related quality of life (HRQoL) of the participants. Results: Total of 199 subjects was included in the study. The mean age of study subjects was 62.1±14.8 years. When looked into the 12 component model of AIMS 2 it was evident that arthritis pain had the highest negative impact on quality of life with a median score of 7.12. This was followed by difficulty in walking and bending (median score 6.6) and tension in life (median score 6.06). Arthritis had low impact in the domains of work, arm movements, household tasks, hand and finger function and self-care tasks. The five component model also reemphasizes the above finding with ‘symptoms’ of arthritis contributing the most to quality of life whereas the domain of ‘role’ contributing the least to quality of life. Conclusions: Over all arthritis had a significant impact on quality of life. Arthritis pain had the highest negative impact on quality of life. This was followed by difficulty in walking and bending and tension in life.